Bridging the troubled waters of tourism studies: from social capital and rural community development to livelihood sovereignty. (18th May 2022) - Naylor, Ryan S.; Hunt, Carter A.; Zimmerer, Karl S.
Through critical concept-building and ethnographic research, we examine how livelihood sovereignty is influenced by tourism development in rural coastal Alaska. Various scales of cruise tourism in this region provide an opportunity to explore theoretical ideas regarding how residents mobilise social capital to secure livelihood sovereignty during dynamic economic transition, climate instability, and socio-cultural change. Our rich ethnographic descriptions outline the unique contributions of bonding, bridging, and linking forms of social capital to this process. By favouring small-scale niche cruises, the study community was better poised to protect cherished identity, integrate tourism sustainably into existing livelihoods, and ensure greater community well-being than is occurring with the large cruise tourism development characterising neighbouring communities. This empirical introduction of the emerging concept of livelihood sovereignty to the tourism studies literature provides important theoretical, methodological, and practical contributions that will be relevant to scholars of tourism and of the Arctic region more broadly.